Eksplorasi Kesejahteraan Anak melalui Interaksi Digital dan Dukungan Keluarga pada Masa Transisi Sosial Kontemporer - Maesaroh Maesaroh; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
In the context of digital interactions and family support during the current social transition, child well-being is the subject of this study. Children's psychological, social, and emotional health can be affected by the development of digital technology, which has changed the way children interact within their families and social environments. A case study method was used in this study to understand children's experiences in using digital technology and the role of families in providing adequate support. Primary data were collected through observation, in-depth interviews, and documentation of children and parents. The results show that digital interactions have two effects: they can help children's social and cognitive development, but they can also harm psychological well-being if not used appropriately. It is evident that active parental involvement, appropriate supervision, open communication, and strong family support are crucial for children's health. Therefore, this study suggests that the role of families in accompanying children and the use of digital technology must be balanced to create an environment that supports optimal child development